PLACE OF THE TRILOGY «MANAS» IN THE KYRGYZ EPIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The study of all the phenomena of the formation of the epic creativity of the Kyrgyz is an important methodological basis of modern literature. It is known that the origins of the formation of Kyrgyz literary criticism, as well as literary criticism of the peoples of the world, were formed in several stages. The trilogy of the Kyrgyz “Manas» is closely connected with folklore and literature. In this sense, the trilogy of «Manas» Kyrgyz consists of archaic-mythical, historical-heroic and many other layers of epic art and absorbed subsequent historical events and genres. In turn, writing led to the development of literary genres (epics, lyrics, dramas) in folk epics.
Keywords: trilogy "Manas", epic, folklore, literature, epic poetry, folklore, literary criticism, oral creativity, written literature, etc.